Comparison between canlite stabilized laterite and probase stabilized laterite - Teck Wei, Ng (2014)
In the previous studies, the unconfined compressive strength (UCS) of Laterite soil was improved significantly by adding polymer soil stabilizers like Canlite and Probase. Although this is the important finding of the research, there is still no comparison study done between the two polymer soil stabilizers. The aim of this paper is to investigate the effectiveness of the Laterite soil stabilization treated by Canlite-liquid and Probase-liquid soil stabilizer. A testing programme, scheduled to achieve the overall objectives of this study was to determine the basic properties of Laterite soil, establish the relationship between the compaction characteristics (maximum dry density and optimum moisture content) with the amount of polymer emulsion and last but not least compare the strength of the Canlite-treated and Probase-treated Laterite soil. The effects of both polymer soil stabilizer – Canlite and Probase were examined. The optimum moisture content of the mixtures was used as a reference to determine the water content for preparing all the specimens and later used in unconfined compressive strength (UCS) test. The laboratory test results showed that the additional amount of Canlite and Probase improved the physical properties, liquid limit and unconfined compressive strength (UCS) of Laterite soil. The compressive strength of the treated Laterite was varied and depends on the type of stabilizers, quantity of additives and curing time. From the UCS tests, it was found that the Probase improve the greater strength of the Laterite as compared to the Canlite